Polynya impacts on water properties in a Northeast Greenland fjord. (5th February 2015) - Dmitrenko, Igor A.; Kirillov, Sergey A.; Rysgaard, Søren; Barber, David G.; Babb, David G.; Pedersen, Leif Toudal; Koldunov, Nikolay V.; Boone, Wieter; Crabeck, Odile; Mortensen, John
Abstract: Polynyas are an important yet poorly understood phenomena of high latitude oceans. A storm event during late December 2013 with down-fjord winds of up to 25 m/s forced the collapse of the landfast ice over the Young Sound (YS) fjord outlet in northeast Greenland. This storm created a coastal polynya that was further maintained by several consecutive wind events until early March 2014. During the polynya period, three landfast ice-tethered oceanographic moorings recorded an enhanced surface layer (∼0–40 m) transport towards the mouth of YS and a layer below (∼40–140 m) flowing into the fjord and supplying the interior with cool and saline water from the polynya. Subsequent CTD transects in May 2014 reveal that this lower layer contained polynya originated cool, saline and oxygen enriched water with oxygen concentrations significantly exceeding values from the previous summer. Salt balance bulk estimates show that the polynya generated a sufficient amount of brine to ventilate the fjord interior.